2020
DOI: 10.1177/1476127020980969
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and practices of interviewing business elites

Abstract: Interviews are an important method for studying a wide range of phenomena, especially those that directly involve members of the so-called business elite, which typically includes CEOs, top managers, and boards of directors. While it is necessary to get close to these actors and their settings for gaining valuable research insights, interviews are challenging interactions to accomplish. Even when one has negotiated access, members of the business elite are typically time-constrained, knowledgeable, used to bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Types of text range from internal documents or histories (Dalpiaz & Di Stefano, 2018; Vaara et al., 2010) to external media reports (Tienari et al., 2003). Talk comes from interviews (Ezzamel & Willmott, 2008; Ma et al., 2020; Vaara et al., 2004) or audio/video recordings (Samra‐Fredericks, 2003; Wenzel & Koch, 2018). These words are analysed through various frames, for instance, those of rhetoric (Sillince et al., 2012; Sorsa & Vaara, 2020) or narratives (Dalpiaz & Di Stefano, 2018; Fenton & Langley, 2011) or performativity (Gond et al., 2018).…”
Section: Mapping the Structure Of The Sap Fieldmentioning
confidence: 99%
“…Types of text range from internal documents or histories (Dalpiaz & Di Stefano, 2018; Vaara et al., 2010) to external media reports (Tienari et al., 2003). Talk comes from interviews (Ezzamel & Willmott, 2008; Ma et al., 2020; Vaara et al., 2004) or audio/video recordings (Samra‐Fredericks, 2003; Wenzel & Koch, 2018). These words are analysed through various frames, for instance, those of rhetoric (Sillince et al., 2012; Sorsa & Vaara, 2020) or narratives (Dalpiaz & Di Stefano, 2018; Fenton & Langley, 2011) or performativity (Gond et al., 2018).…”
Section: Mapping the Structure Of The Sap Fieldmentioning
confidence: 99%
“…Interviewee role diversity was important to view the phenomenon from different angles, thus establishing a spherical understanding of the phenomenon within each case (Yin, 2018). In most cases, repeat interviews were carried out to allow the same respondents to articulate their meanings on changes in family social capital across the two crises (Ma, Seidl, & McNulty, 2020). In-depth interviews were carried out at two separate times, namely June to August 2018 (phenomenon linked to the debt crisis) and November 2020 to February 2021 (phenomenon linked to the Covid-19 pandemic).…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…The challenge of not being understood or, worse still, of holding no relevance, has been widely recognised by a number of scholars (Hirsch, 1995; Useem, 1995; Harvey, 2011; Empson, 2018; Tsui, 2021). Ma et al (2020, p. 62) poignantly observed that whilst “it is powerful for advancing research interviewing business elites, it is widely recognised to be challenging, which might undermine the quality of data collected. Business elites are typically time‐constrained, knowledgeable, used to being dominant in interaction, often visible public figures with reputations at stake, and hence involved in impression management.”…”
Section: Choosing a Point Of Departure For Governance Researchmentioning
confidence: 99%